Bring on the Books for Everybody How Literary Culture Became Popular Culture - Collins, Jim (Duke University Press, 2010)
Bring on the Books for Everybody is an engaging assessment of the robust popular literary culture that has developed in the United States during the past two decades. Jim Collins describes how a once solitary and print-based experience has become an exuberantly social activity, enjoyed as much on the screen as on the page. Fueled by Oprah's Book Club, Miramax film adaptations, superstore bookshops, and new technologies such as the Kindle digital reader, literary fiction has been transformed into best-selling, high-concept entertainment. Collins highlights the infrastructural and cultural changes that have given rise to a flourishing reading public at a time when the future of the book has been called into question. Book reading, he claims, has not become obsolete; it has become integrated into popular visual media.Collins explores how digital technologies and the convergence of literary, visual, and consumer cultures have changed what counts as a "literary experience" in phenomena ranging from lush film adaptations such as The English Patient and Shakespeare in Love to the customer communities at Amazon. Central to Collins's analysis and, he argues, to contemporary literary culture, is the notion that refined taste is now easily acquired; it is just a matter of knowing where to access it and whose advice to trust. Using recent novels, he shows that the redefined literary landscape has affected not just how books are being read, but also what sort of novels are being written for these passionate readers. Collins connects literary bestsellers from The Jane Austen Book Club and Literacy and Longing in L.A. to Saturday and The Line of Beauty, highlighting their depictions of fictional worlds filled with avid readers and their equations of reading with cultivated consumer taste.